Emodin Inhibits the Proliferation of MCF-7 Human Breast Cancer Cells Through Activation of Aryl Hydrocarbon Receptor (AhR) - Zhang, Ning; Wang, Jiawen; Sheng, Aimin; Huang, Shuo; Tang, Yanyan; Ma, Shitang; Hong, Ge (Frontiers in Pharmacology, 2021)
Natural products have proved to be a promising source for the development of potential anticancer drugs. Emodin, a natural compound from Rheum palmatum Linn is used to treat several types of cancers including lung, liver, and pancreas cancers. However, there are few reports about its use in the treatment of breast cancer. Thus, the therapeutic effect and mechanism of emodin on MCF-7 human breast cancer cells were investigated in this research. Morphology observation and cell viability were evaluated to determine the anti-proliferation activity. Network pharmacology and molecular docking were performed to screen the potential targets. Western blot analysis was used to explore its possible antitumor mechanism. The results showed that emodin (50-100 μmol/L) could significantly inhibit the proliferation of MCF-7 cells in a time- and dose-dependent manner. Furthermore, virtual screening studies indicated that emodin was a potent AhR agonist in chemotherapy for breast cancer. Finally, when MCF-7 cells were treated with emodin (100 μmol/L) for 24 h, the aryl hydrocarbon receptor (AhR) and cytochrome P450 1A1(CYP1A1) protein expression levels were significantly upregulated compared with the control group. Our study indicated that emodin exhibited promising antitumor activity against MCF-7 cells probably through the activation of the AhR-CYP1A1 signaling pathway, which laid a foundation for the application of emodin in breast cancer treatment.